2021
DOI: 10.1093/geront/gnab174
|View full text |Cite
|
Sign up to set email alerts
|

Can Automated Vehicles Be Useful to Persons Living With Dementia? The Perspectives of Care Partners of People Living With Dementia

Abstract: Background and Objectives Driving cessation is a complex challenge with significant emotional and health implications for people with dementia, which also affects their family care partners. Automated vehicles (AVs) could potentially be used to delay driving cessation and its adverse consequences for people with dementia and their care partners. Yet, no study to date has investigated whether care partners consider AVs to be potentially useful for people with dementia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Similar notions of the greater perceived benefits of FAVs for people with dementia compared to PAVs were also observed in the results of our qualitative analysis, where people with dementia highlighted additional incentives for FAV use compared to PAV use, including personal freedom, liberty to engage in nondriving tasks, and unloading family care-partners’ responsibilities. The latter was congruent with the findings of previous research on care-partners perspectives of AV use by people with dementia in their care, where compared to PAVs, FAVs were deemed more useful by family care-partners of people with dementia in unloading their caregiving responsibilities ( Haghzare et al, 2022 ). Similarly, people with dementia noted different levels of benefits for PAVs versus FAVs in helping their transition to nondriving.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar notions of the greater perceived benefits of FAVs for people with dementia compared to PAVs were also observed in the results of our qualitative analysis, where people with dementia highlighted additional incentives for FAV use compared to PAV use, including personal freedom, liberty to engage in nondriving tasks, and unloading family care-partners’ responsibilities. The latter was congruent with the findings of previous research on care-partners perspectives of AV use by people with dementia in their care, where compared to PAVs, FAVs were deemed more useful by family care-partners of people with dementia in unloading their caregiving responsibilities ( Haghzare et al, 2022 ). Similarly, people with dementia noted different levels of benefits for PAVs versus FAVs in helping their transition to nondriving.…”
Section: Discussionsupporting
confidence: 89%
“…AV testing among people with dementia can additionally help inform governmental standards on AV development, specific AV designs, and AV licensing and training for people with dementia, which are not only required to ensure the accessibility and safety of AVs for people with dementia but were also highlighted in this study by people with dementia as a potential means to overcome their hesitancies to use AVs. AV testing among people with dementia could also help alleviate the concerns of care-partners identified in previous research pertaining to potential challenges that people with dementia in their care may face when using AVs ( Haghzare et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Highly AVs that correspond to levels 4 and 5 as defined by the Society of Automotive Engineers (SAE International, 2021) offer full driving automation, with no requirement for the users to take over driving. As such, highly AVs can serve as assistive technologies that perform all basic driving tasks for individuals with MCI or dementia, and therefore, relieve them from manual control of the vehicle (Haghzare et al, 2021). This can allow individuals with MCI to travel by themselves and possibly increase their independence and mobility.…”
Section: Introductionmentioning
confidence: 99%
“…However, these types of higher order activities may introduce new challenges since they may be dependent on memory and decision-making ability and present a new barrier to safe and efficient use by individuals with MCI. For example, a study by Haghzare et al (2021) exploring dementia patients' care partners' perceptions of AVs revealed that people with dementia may face challenges in navigating any pre-trip-or post-trip-related tasks, such as negotiating pick-up and drop-off locations. They also concluded that these shortcomings are due to the fact that AVs are not designed as assistive technologies specifically for people with cognitive impairments.…”
Section: Introductionmentioning
confidence: 99%